Islamic Values in Conservation Biology: Feasibility Analysis of a Religious-Integrated Textbook for Biology Education - Angela, Lia; Alfian, Muhammad (Department of Biology Education, Faculty of Education and teacher Training, Maritime University of Raja Ali Haji, 2024)
This study aims to analyze the feasibility of a conservation biology textbook that integrates Islamic values into biology education. The textbook was developed to provide a deeper understanding of conservation biology through a faith-based approach, relevant to higher education. The feasibility analysis involved language and media experts, covering linguistic, presentation, and graphic aspects. The results showed an average score of 95.40% for linguistic aspects, 90.80% for presentation aspects, and 90.50% for graphic aspects, all of which fall into the